The T-box transcription factor brachyury behaves as a tumor suppressor in gliomas - Pinto, Filipe (2021)
The oncogene brachyury (TBXT) is a T-box transcription factor that is overexpressed in multiple solid tumors and is associated with tumor aggressiveness and poor patient prognosis. Gliomas comprise the most common and aggressive group of brain tumors, and at the present time the functional and clinical impact of brachyury expression has not been investigated previously in these neoplasms. Brachyury expression (mRNA and protein) was assessed in normal brain (n = 67), glioma tissues (n = 716) and cell lines (n = 42), and further in silico studies were undertaken using genomic databases totaling 3115 samples. Our glioma samples were analyzed for copy number (n = 372), promoter methylation status (n = 170), and mutation status (n = 1569 tissues and n = 52 cell lines) of the brachyury gene. The prognostic impact of brachyury expression was studied in 1524 glioma patient tumors. The functional impact of brachyury on glioma proliferation, viability, and cell death was evaluated both in vitro and in vivo. Brachyury was expressed in the normal brain, and significantly downregulated in glioma tissues. Loss of brachyury was associated with tumor aggressiveness and poor survival in glioma patients. Downregulation of brachyury was not associated with gene deletion, promoter methylation, or inactivating point mutations. Brachyury re-expression in glioma cells was found to decrease glioma tumorigenesis by induction of autophagy. These data strongly suggest that brachyury behaves as a tumor suppressor gene in gliomas by modulating autophagy. It is important to note that brachyury constitutes an independent positive biomarker of patient prognosis. Our findings indicate that the role of brachyury in tumorigenesis may be tissue-dependent and demands additional investigation to guide rational interventions. (c) 2020 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.